Ekstraksi Limbah Serutan Kayu Matoa (Pometia pinnata) sebagai Zat Warna Alam pada Pewarnaan Kain Batik Serat Protein - Agus Haerudin; Yudi Satria (Seminar Nasional Teknik Kimia Kejuangan, 2018)
Phytochemical analysis results showed that the extract of bark matoa contains flavonoids, and tannins compounds, the chemical content of these plants has the potentially as a source of natural dyes, while wood shavings waste from matoa wood company in Jayapura-Papua very overflow and not yet optimally utilized. The purpose of this research is to know the direction of the color resulting from the extraction of the waste of wood matoa shavings on batik cloth of protein fiber (silk), with the quality standard seen from the test value of the color fastness on the washing, the color difference (L*, a* , b*) and the color degree. This research using expiriment method, the extraction temperature (75°C dan 100°C), with variations in dye solution pH (acid 4 and base 10), as well as variations of the final mordant substance (70 g/l of alum and tunjung 30 g/l). The result of the research was found that the extraction temperature had no significant effect on the test value, whereas the acid and base pH variation treatment in dye solution had an effect on the degree of color and color direction, whereas acid pH produces the direction of dark brown color while base pH produces the direction of light brown color, color fastness test against washing showed 4-5 in good category.